A high-throughput preparation method and application of a high-entropy alloy

CN117577231BActive Publication Date: 2026-10-27NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311400150.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2026-10-27
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

[0004]为了解决现有技术中针对高熵合金设计需要高效率的实验方法,同时现有的扩散偶高通量实验法虽然可以满足在单次制备条件下对多个合金成分进行表征,但仍然存在固相之间的扩散相对较慢,为了在扩散偶界面处得到预设的梯度变化区域,需要对样品进行长时间的热处理的技术问题

Benefits of technology

[0030]本发明提供了一种新的高通量制备方法,在新合金成分探索方面,相较于传统的试错法具有更高的效率。该方法在轻质高强高熵合金高性能成分筛选中能发挥极大作用,也适用于其他金属材料的高通量成分设计与制备。本发明所提出的液态金属浸入法,相较于常规的固-固扩散偶法,不仅操作简单、成本较低,并且可制备出更宽的成分梯度层,有利于精细化成分分析,并能够产生更多的性能数据点,从而提高了高通量成分筛选的精度与可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117577231B_ABST
    Figure CN117577231B_ABST
Patent Text Reader

Abstract

The application discloses a high-flux preparation method of a high-entropy alloy and application thereof, and relates to the technical field of alloy materials. The method comprises the following steps: presetting the alloy element composition of a base high-entropy alloy and the atomic percentage of each alloy element; performing high-flux preparation through a liquid metal immersion method; screening the high-entropy alloy performance according to a variable element content-nano hardness diagram, a variable element content-Young's modulus diagram and a variable element content-density diagram, and determining the optimal composition of the high-entropy alloy. The application can play a great role in the high-performance composition screening of light, high-strength and high-entropy alloys, and is also suitable for the high-flux composition design and preparation of other metal materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy materials technology, specifically to a high-throughput preparation method and application of high-entropy alloys. Background Technology

[0002] High-entropy alloys are a novel type of alloy that breaks through traditional alloy design concepts, composed of multiple metallic elements in specific proportions. Due to their high hardness, high strength, and good thermal stability, high-entropy alloys have a wide range of applications in engineering materials. However, in the design process of high-entropy alloy materials, the alloy composition varies complexly due to their multi-principal element characteristics, and the alloy properties are greatly affected by the constituent elements and composition. How to achieve rapid screening for performance optimization of high-entropy alloys is a crucial issue in current high-entropy alloy research. In the design of lightweight high-entropy alloys, doping with low-density elements (such as Al and Ti) in conventional refractory high-entropy alloys is considered an important method. However, determining the specific doping percentage using conventional trial-and-error experiments is costly and time-consuming, hindering the development of novel alloy compositions. Therefore, designing a high-throughput method applicable to high-entropy alloys to characterize multiple alloy compositions under single-preparation conditions is of great significance.

[0003] In current high-throughput metallurgical synthesis of alloys, the diffusion couple method—which involves systematically mixing a pre-defined alloy solid block to achieve high-throughput preparation—is an important research direction. Compared to other methods, high-throughput preparation via thermal diffusion offers advantages such as obtaining a continuously distributed gradient region and lower material preparation costs. However, the diffusion couple method involves diffusion between two solids, which necessitates a very good interfacial bond. This places high demands on the smoothness, roughness, and purity of the pre-defined alloy sample surface, resulting in high costs. Furthermore, diffusion between solid phases is relatively slow, requiring prolonged heat treatment of the sample to obtain the desired gradient region at the diffusion couple interface. Summary of the Invention

[0004] To address the need for efficient experimental methods in the design of high-entropy alloys, and while existing high-throughput diffusion couple methods can characterize multiple alloy components in a single preparation, they still suffer from relatively slow diffusion between solid phases. Furthermore, obtaining the desired gradient change region at the diffusion couple interface requires prolonged heat treatment of the sample. This invention provides a high-throughput preparation method for high-entropy alloys, achieving high-throughput preparation of high-entropy alloy samples through solid-liquid two-phase diffusion, enabling rapid screening for performance optimization of high-entropy alloys with greater efficiency.

[0005] The first objective of this invention is to provide a high-throughput preparation method for high-entropy alloys, comprising the following steps:

[0006] The alloy element composition of the pre-defined high-entropy alloy matrix and the atomic percentage of each alloy element;

[0007] Based on the alloy element composition of the preset matrix high-entropy alloy and the atomic percentage of each alloy element, the metal element as the variable is determined.

[0008] Based on the alloy element composition of the matrix high-entropy alloy, the atomic percentage of each alloy element, and the metal element as a variable, high-throughput preparation is carried out by liquid metal immersion method.

[0009] The samples prepared by high-throughput processing were characterized, and variable element content-nanohardness diagram, variable element content-Young's modulus diagram, and variable element content-density diagram were plotted based on the characterization results.

[0010] Based on the variable element content-nano hardness diagram, variable element content-Young's modulus diagram, and variable element content-density diagram, the properties of high-entropy alloys are screened to determine the optimal composition of high-entropy alloys.

[0011] Preferably, the method for determining the metallic element of the variable includes:

[0012] The metal elements of the variables are determined based on the preset high-entropy matrix alloy and the analysis of the target performance and mechanism.

[0013] The melting point of the variable metallic element is 200°C or more lower than the melting point of the matrix high-entropy alloy.

[0014] Preferably, the high-throughput preparation via liquid metal immersion includes:

[0015] Based on the pre-defined alloy element composition of the matrix high-entropy alloy and the atomic percentage of each alloy element, the matrix high-entropy alloy is prepared by arc melting, and then processed and surface-treated.

[0016] The variable metallic element is processed and surface-treated. The matrix high-entropy alloy and the variable metallic element are placed in a vacuum container, smelted, and then water-cooled to obtain a high-throughput sample.

[0017] More preferably, in the high-throughput sample preparation process, after heating the variable metal element to a liquid state, the matrix high-entropy alloy sample is completely immersed.

[0018] More preferably, the high-entropy matrix alloy and the variable metallic element are placed in a vacuum container and subjected to a melting process, including:

[0019] The melting temperature is greater than the melting point of the variable metal element, but less than the melting point of the base high-entropy alloy by 200°C or more.

[0020] Preferably, the characterization results include: performing nanoindentation tests on the prepared high-throughput sample, selecting load points from the inside out, measuring the nanohardness and reduced modulus at each load point; and the content of variable metal elements at each load point.

[0021] More preferably, the plotting of the variable element content-density map includes:

[0022] The theoretical density of the high-entropy alloy is obtained by considering the atomic percentage, atomic mass, and density of each alloying element at the loading point.

[0023] A variable element content-density diagram was drawn based on the variable metal element content and the theoretical density of the high-entropy alloy.

[0024] More preferably, the Young's modulus at each load point is obtained based on the reduced modulus at each load point;

[0025] The variable metal element content at each load point is plotted with its corresponding nanohardness and Young's modulus to create variable element content-nanohardness and variable element content-Young's modulus plots.

[0026] Preferably, the screening method includes:

[0027] By constructing variable element content-nanohardness maps and variable element content-Young's modulus maps, the composition range of high-entropy alloys with high nanohardness or high Young's modulus is determined. Then, by using variable element content-density maps, the optimal high-entropy alloy composition with low density, high hardness, and Young's modulus is finally determined.

[0028] A second objective of this invention is to provide an application of the above-described method in the design of high-entropy alloy compositions.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] This invention provides a novel high-throughput preparation method that is more efficient than traditional trial-and-error methods in exploring new alloy compositions. This method plays a significant role in screening high-performance components for lightweight, high-strength, and high-entropy alloys, and is also applicable to high-throughput composition design and preparation of other metallic materials. The liquid metal immersion method proposed in this invention, compared to the conventional solid-solid diffusion couple method, is not only simpler to operate and lower in cost, but also allows for the preparation of a wider composition gradient layer, which is beneficial for refined composition analysis and generates more performance data points, thereby improving the accuracy and reliability of high-throughput composition screening. Attached Figure Description

[0031] Figure 1 A schematic diagram illustrating the principle of the high-throughput preparation method for high-entropy alloys provided by this invention;

[0032] Figure 2 The image shows the microstructure of the high-entropy alloy sample prepared by liquid metal immersion method, including scanning electron microscopy (SEM) images and line scan results.

[0033] Figure 3 This is a schematic diagram of the selected loading points for high-throughput sample characterization in the example.

[0034] Figure 4 To conduct high-throughput experiments on the Al-HfNbTaTiZr system, aluminum element content-nanohardness diagram, aluminum element content-Young's modulus diagram, and aluminum element content-density diagram were plotted based on the experimental results. Detailed Implementation

[0035] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention, but the embodiments are not intended to limit the present invention.

[0036] This invention relates to a high-throughput preparation method for high-entropy alloys, which mainly includes three parts: (1) High-throughput preparation: selecting a suitable high-entropy alloy system and variable elements; achieving high-throughput preparation through liquid immersion method; (2) High-throughput characterization: performing high-throughput composition and performance characterization on the prepared samples; (3) Composition screening: drawing a performance-element content curve based on the results, and referring to the curve, quickly screening high-entropy alloy components with high performance or desired performance. The details are as follows.

[0037] This invention provides a high-throughput preparation method for high-entropy alloys, comprising the following steps:

[0038] The alloy element composition of the pre-defined high-entropy alloy matrix and the atomic percentage of each alloy element;

[0039] Based on the alloy element composition of the preset matrix high-entropy alloy and the atomic percentage of each alloy element, the metal element as the variable is determined.

[0040] Based on the alloy element composition of the matrix high-entropy alloy, the atomic percentage of each alloy element, and the metal element as a variable, high-throughput preparation is carried out by liquid metal immersion method.

[0041] The samples prepared by high-throughput processing were characterized, and variable element content-nanohardness diagram, variable element content-Young's modulus diagram, and variable element content-density diagram were plotted based on the characterization results.

[0042] Based on the variable element content-nano hardness diagram, variable element content-Young's modulus diagram, and variable element content-density diagram, the properties of high-entropy alloys are screened to determine the optimal composition of high-entropy alloys.

[0043] The method for determining the metallic element of the variable includes:

[0044] The metal elements of the variables are determined based on the preset high-entropy matrix alloy and the analysis of the target performance and mechanism.

[0045] The melting point of the variable metallic element is 200°C or more lower than the melting point of the matrix high-entropy alloy.

[0046] It should be noted that the melting point of the variable metallic element is T1, and the melting point of the matrix high-entropy alloy is T2. <T2-200K。

[0047] The high-throughput preparation via liquid metal immersion includes:

[0048] Based on the pre-defined alloy element composition of the matrix high-entropy alloy and the atomic percentage of each alloy element, the matrix high-entropy alloy is prepared by arc melting, and then processed and surface-treated.

[0049] The variable metallic element is processed and surface-treated. The matrix high-entropy alloy and the variable metallic element are placed in a vacuum container, smelted, and then water-cooled to obtain a high-throughput sample.

[0050] The vacuum level in the vacuum container should be as low as 10. -4 Below Pa.

[0051] In one embodiment, the high-throughput preparation via liquid metal immersion is achieved through the following steps:

[0052] Based on the pre-defined alloy element composition of the matrix high-entropy alloy and the atomic percentage of each alloy element, the matrix high-entropy alloy is prepared and cut to obtain a matrix high-entropy alloy sample. The sample is then mechanically ground and polished until its surface is flat and smooth.

[0053] A certain mass of surface-treated variable metallic element and a high-entropy matrix alloy block are vacuum-sealed together.

[0054] The tube was sealed and kept at a specific temperature for 24 hours, and then water-cooled to obtain a high-throughput sample with a layered structure at the microscopic level.

[0055] Among them, the purity of the elemental metals used in the smelting of the high-entropy matrix alloy, as well as the variable elemental metals, must be ≥99.9%.

[0056] Specifically, in the high-throughput sample preparation process, the variable metal element is heated to a liquid state and then completely immersed in the matrix high-entropy alloy sample.

[0057] In one embodiment, the mass of the added variable metal element is required to completely immerse the high-entropy matrix alloy sample when the variable metal element is converted into a liquid state.

[0058] The process involves placing the high-entropy matrix alloy and the variable element in a vacuum container and undergoing a melting process. This includes a melting temperature greater than the melting point of the variable element but less than the melting point of the high-entropy matrix alloy by 200°C or more. It should be noted that if the melting point of the variable element is T1 and the melting point of the high-entropy matrix alloy is T2, then the required melting temperature and heat treatment temperature T is: T1 <T<T2-200K。

[0059] According to the present invention, the characterization results include: performing nanoindentation tests on the prepared high-throughput sample, selecting load points from the inside out, and measuring the nanohardness and reduced modulus at each load point; as well as the content of variable metal elements at each load point. Elemental analysis of each load point is performed using X-ray energy dispersive spectroscopy to measure the content of variable metal elements at each load point.

[0060] The drawing of the variable element content-density plot includes:

[0061] The theoretical density of the high-entropy alloy is obtained by considering the atomic percentage, atomic mass, and density of each alloying element at the loading point.

[0062] A variable element content-density diagram was drawn based on the variable metal element content and the theoretical density of the high-entropy alloy.

[0063] Among them, each alloying element at the load point includes all elements of the matrix high-entropy alloy and the variable metal species.

[0064] In one embodiment, the density and the content of each element at each load point should satisfy the following relationship:

[0065]

[0066] In the formula, ρ represents the density of the alloy; c i A represents the atomic percentage of each alloying element at the load point. i ρ represents the atomic mass of each alloying element at the load point. i This indicates the density of each alloying element at the load point.

[0067] Specifically, the Young's modulus at each load point is obtained based on the reduced modulus at each load point;

[0068] In one embodiment, the conversion of the reduced modulus at each load point to Young's modulus is calculated using the following formula:

[0069]

[0070] In the formula, E s The Young's modulus of the tested material; v S E represents the Poisson's ratio of the tested material.r V represents the measured reduced modulus. i and E i E represents the Young's modulus and Poisson's ratio of the indenter material. For diamond indenters, E i =1140GPa,v i =0.07.

[0071] The variable metal element content at each load point is mapped one-to-one with its corresponding nanohardness and Young's modulus to create variable element content-nanohardness and variable element content-Young's modulus diagrams.

[0072] The screening method is as follows:

[0073] To obtain lightweight, high-hardness, high-modulus, and high-entropy alloys, the composition range of high-entropy alloys with high nanohardness or high Young's modulus can be determined by constructing variable element content-nanohardness maps and variable element content-Young's modulus maps. Then, the optimal high-entropy alloy composition with low density, high hardness, and Young's modulus can be finally determined by using variable element content-density maps.

[0074] The present invention also provides an application of the method described in claim 1 in the design of high-entropy alloy compositions.

[0075] The following examples use an Al-HfNbTaTiZr alloy as an example to illustrate the method provided by the present invention.

[0076] Example 1

[0077] A high-throughput preparation method for high-entropy alloys, see [link to relevant documentation]. Figure 1 As shown, it includes the following steps:

[0078] In this embodiment, based on the given Al-HfNbTaTiZr alloy composition system, a refractory high-entropy alloy of HfNbTaTiZr was prepared using elemental Hf, Nb, Ta, T, and Zr with a purity higher than 99.9% via vacuum arc melting. The resulting block sample was cut to obtain dimensions of 25×6×6mm. 3 After surface treatment, the sample was vacuum-sealed together with a 5g aluminum block at a vacuum level of 10. -4 Pa. The sealed tube was heat-treated at 950℃ for 24 h, and finally annealed to obtain a high-throughput sample. The high-throughput sample was obtained and its microstructure was characterized. The curves showing the changes in nanohardness, Young's modulus, and density with Al element content were obtained. Finally, a lightweight multi-principal element alloy with high hardness and high modulus was designed. 56 Hf 10 Nb7Ta9Ti6Zr12 The specific steps are as follows:

[0079] Step 1: Utilize Figure 1 The method shown enables high-throughput preparation of Al-HfNbTaTiZr alloy samples, yielding high-throughput samples with microscopic layered structures, such as... Figure 2 As shown.

[0080] Step 2: Select loading points at the transition layer interface of the high-throughput sample for nanoscale testing, such as... Figure 3 As shown, the nanohardness and reduced modulus of each point are obtained. The Young's modulus value is obtained according to formula (1). Energy spectroscopy analysis is performed on the composition of each load point to determine the elemental composition of each point.

[0081] Step 3: Based on the characterization results of each load point, plot the nanohardness-aluminum content diagram and the Young's modulus-aluminum content diagram, such as... Figure 4 As shown in (a) and (b), and based on the relative atomic masses and density values ​​of the six elements Al, Hf, Nb, Ta, Ti, and Zr, the theoretical density corresponding to each load point is obtained according to formula (2), and an alloy density-aluminum content diagram is plotted, as shown in the figure. Figure 4 As shown in (c).

[0082] Step 4: Based on the performance prediction chart, determine the Al composition of the lightweight multi-principal element alloy with high hardness and high modulus. 56 Hf 10 Nb7Ta9Ti6Zr 12 According to high-throughput characterization results, this component has a nanohardness of 14.92 GPa, a Young's modulus of 156.79 GPa, and a theoretical density of 6.277 g / cm³. 3 According to literature review, the alloy composition prepared and screened by this high-throughput method has the highest hardness and low density among lightweight refractory high-entropy alloys, and has important application prospects in the fields of high-temperature structural materials and heat-resistant coatings.

[0083] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A high-throughput preparation method for high-entropy alloys, characterized in that, Includes the following steps: The alloy element composition of the pre-defined high-entropy alloy matrix and the atomic percentage of each alloy element; Based on the alloy element composition of the preset matrix high-entropy alloy and the atomic percentage of each alloy element, the metal element as the variable is determined. Based on the alloy element composition of the matrix high-entropy alloy, the atomic percentage of each alloy element, and the metal element as a variable, high-throughput preparation is carried out by liquid metal immersion method. The samples prepared by high-throughput processing were characterized, and variable element content-nanohardness diagram, variable element content-Young's modulus diagram, and variable element content-density diagram were plotted based on the characterization results. Based on the variable element content-nano hardness diagram, variable element content-Young's modulus diagram, and variable element content-density diagram, the properties of high-entropy alloys are screened to determine the optimal composition of high-entropy alloys.

2. The high-throughput preparation method of high-entropy alloys according to claim 1, characterized in that, The method for determining the metallic element of the variable includes: The metal elements of the variables are determined based on the preset high-entropy matrix alloy and the analysis of the target performance and mechanism. The melting point of the variable metallic element is 200°C or more lower than the melting point of the matrix high-entropy alloy.

3. The high-throughput preparation method of high-entropy alloys according to claim 1, characterized in that, The high-throughput preparation via liquid metal immersion includes: Based on the pre-defined alloy element composition of the matrix high-entropy alloy and the atomic percentage of each alloy element, the matrix high-entropy alloy is prepared by arc melting, and then processed and surface-treated. The variable metallic element is processed and surface-treated. The matrix high-entropy alloy and the variable metallic element are placed in a vacuum container, smelted, and then water-cooled to obtain a high-throughput sample.

4. The high-throughput preparation method of high-entropy alloys according to claim 3, characterized in that, In the high-throughput sample preparation process, the variable metal element is heated to a liquid state and then completely immersed in the high-entropy alloy matrix sample.

5. The high-throughput preparation method of high-entropy alloys according to claim 3, characterized in that, The high-entropy matrix alloy and the variable metallic element are placed in a vacuum container and subjected to a melting process, including: The melting temperature is greater than the melting point of the variable metal element, but less than the melting point of the base high-entropy alloy by 200°C or more.

6. The high-throughput preparation method of high-entropy alloys according to claim 1, characterized in that, The characterization results include: performing nanoindentation tests on the prepared high-throughput samples, selecting load points from the inside out, measuring the nanohardness and reduced modulus at each load point; and the content of variable metal elements at each load point.

7. The high-throughput preparation method of high-entropy alloys according to claim 6, characterized in that, The drawing of the variable element content-density plot includes: The theoretical density of the high-entropy alloy is obtained by considering the atomic percentage, atomic mass, and density of each alloying element at the loading point. A variable element content-density diagram was drawn based on the variable metal element content and the theoretical density of the high-entropy alloy.

8. The high-throughput preparation method of high-entropy alloys according to claim 6, characterized in that, The Young's modulus at each load point is obtained from the reduced modulus at each load point. The variable metal element content at each load point is plotted with its corresponding nanohardness and Young's modulus to create variable element content-nanohardness and variable element content-Young's modulus plots.

9. The application of the method described in any one of claims 1 to 8 in the design of high-entropy alloy compositions.